Nurses’ knowledge, attitude and practice towards ethical decision making in Neonatal Intensive Care Unit at Hospital Universiti Sains Malaysia - Hiong, Ling Sing (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Ethical decision making helps people to make difficult choices when faced with an ethical dilemma, a situation in which there is no clear right or wrong answer. It is inherent in nursing practice. Nurses working in neonatal intensive care unit (NICU) arc often confronted dilemmas concerning issues of patient care management and ethical issues with life sustaining treatment decisions. Therefore, the aim of this study was to investigate nurses' knowledge, attitude and practice of ethical decision making in NICU, Hospital Universiti Sains Malaysia (Hospital USM). A crossscctional survey on nursing staff (n=56) in NICU, HUSM was conducted using a selfadministered structured questionnaire. Data was analyzed using the Statistical Package Social Science (SPSS) version 20.0. Nurses in the study had high knowledge to the principle ethics (M= 11.50, SD= 1.31), high attitude (M= 26.73. SD= 3.15) and satisfactory practice (M= 5.64. SD= 1.14). Chi square test revealed that there was no association between age, marital status, highest education nursing level, years of working experience and current position with knowledge and attitude. The finding also showed that age of nurses (p=0.041) and years of working experience (p=0.041) were significantly associated with practice of the nurses. However the other socio demographic factors were no significant association with practice. The results of this study can serve as the basic to facilitate continuous education and research on ethical decision making among nurses. In conclusion, the study highlights the need to identify professionals in the workforce who appear to be indifferent to ethical and legal issues, to devise means to sensitize them to these issues and appropriately training them.